Status Markers of Lexical Meaning of Verbs with Wide Semantics (on the Material of Russian, German, English Dictionaries) (Proceedings of Southern Federal University. Philology, 2019)
Galina V. Kulikova (Ekaterinburg, Russian Federation)The article discusses the status characteristics of the values of widesemantic words, for example, Russian, English and German verbs, denoting the transfer of an object: брать, давать, take, give, nehmen, geben. It has been analyzed vocabulary articles in various explanatory dictionaries of Russian, English and German. The article allows to see the differences in national lexicographic traditions and ways of displaying the semantics of wide-valued verbs in lexicographic parameters.Key words: semantics, wide-semantic verb, lexical meaning, lexicography.DOI 10.23683/1995-0640-2019-3-89-95